Is primary angioplasty an acceptable alternative to thrombolysis? Quantitative and qualitative study of patient and carer satisfaction - Sampson, Fiona C (Health Expect, 2010)
Objective  The National Infarct Angioplasty Project assessed the feasibility of establishing a comprehensive primary angioplasty service. We aimed to compare satisfaction at intervention hospitals offering angioplasty‐based care and control hospitals offering thrombolysis‐based care. Design  Mixed methods, with postal survey of patients and their carers, supported by semi‐structured interviews. Setting and participants  Survey of 682 patients and 486 carers, and interviews with 33 patients and carers, in eight English hospitals. Interventions  Primary angioplasty or thrombolysis. Main outcome measures  Satisfaction with treatment. Results  Responses were received from 595/682 patients (87%) and 418/486 carers (86%). Satisfaction with overall care was high at both intervention and control sites (78% vs. 71% patients rated their care as ‘excellent’, P = 0.074). Patient satisfaction was higher at intervention sites for some aspects of care such as speed of treatment (80% vs. 67%‘excellent’, P = 0.001). Convenience of visiting was rated lower at intervention sites by carers (12% vs. 1%‘poor’, P = 0.001). During interviews, carers reported that they accepted the added inconvenience of visiting primary angioplasty sites in the context of this life‐saving treatment. Patient satisfaction with discharge and aftercare was lower in both treatment groups than for other aspects of care. Conclusions  Reorganization of care to offer a primary angioplasty service was acceptable to patients and their carers. Satisfaction levels were high regardless of the type of care received, with the exception of discharge and aftercare.